The realistic experience of the limit and the dangerous ambiguity of utopia - Gianfranco Borrelli (Governare la paura, 2016)
In order to investigate the series of relations between the tradition of so-called realism and the writing/practices of utopia in Western philosophical-political culture, it is first necessary to look at the meanings that realism itself takes inside the theoretical reflections on the experience and category of limit. We must therefore look closely at the essential elements of the structural ambiguity of the discourses/practices that refer to utopia as the set of modes of utopic conversion of the subject of modernity. Only then, will we be able to trace the multiple ideologies that presuppose horizons of an (impossible) perfect happiness, as well as the different ways of generating forms of unutterable grief; on one hand, the tragic dystopias produced by the cruelty of the human beast, on the other, the various forms of heterotopias fashioned and practiced by human beings in order to provide sense and relief to the ordinary sorrows of life.